De-dollarizing the Peruvian economy: a portfolio approach - Morón, Eduardo (2003)
Financial dollarization creates design problems for economic policy as increases the level of financial vulnerability. However, countries with high levels of dollarization have done almost nothing to reduce it. In this paper we study two ways to do it and we evaluate them within a model that emphasizes a portfolio approach. We calibrate the model to replicate the Peruvian economy. The two policy options that we consider are: (i) increasing the risk of dollar deposits, reducing the level of coverage in the safety net mechanism; (ii) increasing the relative volatility of inflation vis-à-vis real depreciation. Our results show that the former has the potential risk of lowering the level of financial intermediation, whereas the second might be more effective to de-dollarize the economy.